PENGARUH PENDIDIKAN KESEHATAN DI MEDIA SOSIAL INSTAGRAM TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG ANEMIA DEFISIENSI BESI - Andriani, Astrid Aisha; Maulana, M. Ali; Fradianto, Ikbal; Rahmawati, Nadia; S.U.A, Berthy (School of Nursing, Faculty of Medicine, Tanjungpura University, 2025)
Background: Anemia is a critical health issue that demands urgent attention. In Indonesia, the prevalence of anemia soared to 72.3% in 2018 from 48.9% in 2013. Effective prevention of anemia requires widespread health education. Utilizing video and social media platforms is essential for reaching and educating a broader audience. Objective: A study aimed to assess the impact of health education on Instagram concerning the knowledge of iron deficiency anemia among adolescent girls. Method: This study involving 100 participants, utilized a pre-experimental design with pre-test and post-test assessments. Research instruments included health education videos, social media, and questionnaires. Analysis was conducted using the Wilcoxon test. Result: The results from the Wilcoxon test displayed a considerable increase in knowledge after the Instagram health education initiative. The results indicate a significant increase in knowledge after health education, with a p-value of less than 0.001.. This evidence underscores the positive influence of health education on Instagram in enhancing the understanding of iron deficiency anemia among adolescent girls.